Voices from gender studies
1 online resource.
Keywords: "The book is aimed at providing an assertion of Gender Studies as a vital community in our time, united in a commitment to inquiry. It brings forward an interdisciplinary set of early career researchers' accounts of their motives for engaging in Gender Studies and, of the encounters with limitations as well as possibilities they experience on the paths they have chosen. Each chapter is accompanied by a brief response paper where a more senior researcher involves in conversation with respective chapter's content and shares reflections regarding Gender Studies, its integration and developments. The first level corresponds with the significance of research in the field and its transformative power in and, crucially, outside the academia. The second relates to the value of networking and community building for doing research. The book presents Gender Studies in a communicative, open manner that invites the reader to engage in and continue the displayed discussions. This book will be of interest to students and scholars of gender studies, sociology, queer studies, women's studies, trans studies, anthropology, and literary studies"--